Social Modeling of Food Intake: No Evidence for Moderation by Identification With the Norm Referent Group - Liu, Jinyu; Higgs, Suzanne (Frontiers in Psychology, 2019)
Normative information has a powerful effect on food intake and food selection. People tend to use the eating behaviour of others as a reference for their own eating behaviours and match their intake to an eating partner. This is known as social modelling. There is some evidence to suggest that people are more likely to model a norm when it comes from an in-group than when it comes from an out-group, but whether the strength of identification with a norm referent group moderates modelling of intake has yet to be examined. The current paper presents the results of two studies that investigated whether modelling of intake is moderated by strength of identification with the norm referent group. In Study 1, we recruited 90 female students from the University of Birmingham (UoB) (mean age= 21). Students were allocated to either a low norm condition (presented with a sheet that presented a low cookie intake of previous participants) or a high norm condition (presented with a sheet that presented a high cookie intake of previous participants), or a no norm condition (control group without the sheet containing information about previous participants’ cookie intake). Students also completed a questionnaire on their identification as a Birmingham student and cookie intake was assessed. In Study 2, we recruited 84 students (mean age= 21) who were randomly allocated to one of two conditions (a group presented with a high norm for vegetable intake or no information about a vegetable intake norm). Strong modelling effects were found across both studies but the extent to which the participants identified as a Birmingham University Student did not moderate these effects. The moderating effect of social identity on modelling of eating might be context-dependent.